Numerical Prediction of Chloride Penetration in Concrete Exposed to a Marine Environment at Tide - Sung In Hong; Ki Yong Ann (Advances in Materials Science and Engineering)
Reinforced concrete structures under cyclic exposure to the corrosive environment such as the tidal zone as a part of marine structure entail the higher risk of steel corrosion. In this paper, chloride penetration in concrete exposed to the tidal zone was predicted using a combined moisture and chloride transport model. For the analysis of moisture transport, pore size distribution in concrete was determined from the experimental observation and used to determine the moisture permeability and degree of saturation. Then, the chloride profile through nonsaturated concrete cover was calculated by applying the moisture distribution along the penetration depth to the chloride convection and diffusion model. To assess sensitivity of the service life to the environment and concrete mix conditions, this study used three types of tide levels and water to cement ratios in the simulation. Under 10 years of tidal exposure condition, the minimum required cover depth at which the threshold chloride concentration reaches on the steel embedment increases only about 1.13 times as the tide level increases from the minimum to the highest while that for the w/c ratio increases about 1.69 times.